Fault lines of globalization : legal order and the politics of a-legality - Lindahl, Hans, 1958- (Oxford : Oxford University Press, 2014)
A distinctive contribution to the current debate about the nature of globalisation processes, this book examines the boundaries of legal and constitutional orders and the relationship of these boundary issues to the question of the political foundations and legitimacy of legal orders.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 13, 2013).
Keywords: Law and globalization; Boundaries; Law; International law